Molecular Dynamics Guided Design of Tocoflexol: A New Radioprotectant Tocotrienol with Enhanced Bioavailability. Issue 1 (26th December 2013) - Compadre, Cesar M.; Singh, Awantika; Thakkar, Shraddha; Zheng, Guangrong; Breen, Philip J.; Ghosh, Sanchita; Kiaei, Mahmoud; Boerma, Marjan; Varughese, Kottayil I.; HauerâJensen, Martin; Shankar, Gita N.; Moos, Walter H.
Abstract <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> Preclinical Research </table-wrap> There is a pressing need to develop safe and effective radioprotector/radiomitigator agents for use in accidental or terroristâinitiated radiological emergencies. Naturally occurring vitamin E family constituents, termed tocols, that include the tocotrienols, are known to have radiationâprotection properties. These agents, which work through multiple mechanisms, are promising radioprotectant agents having minimal toxicity. Although Î±âtocopherol (AT) is the most commonly studied form of vitamin E, the tocotrienols are more potent than AT in providing radioprotection and radiomitigation. Unfortunately, despite their very significant radioprotectant activity, tocotrienols have very short plasma halfâlives and require dosing at very high levels to achieve necessary therapeutic benefits. Thus, it would be highly desirable to develop new vitamin E analogues with improved pharmacokinetic properties, specifically increased elimination halfâlife and increased area under the plasma level versus time curve. The short elimination halfâlife of the tocotrienols is related to their low affinity for the Î±âtocopherol transfer protein (ATTP), the protein responsible for maintaining the plasma level of the tocols. Tocotrienols have less affinity for ATTP than does AT, and thus have a longer residence time in the liver, putting them at higher risk for metabolism and biliary excretion. We hypothesized that the lowâbinding affinity of tocotrienols to ATTP is due to the relatively more rigid tail structure of the tocotrienols in comparison with that of the tocopherols. Therefore, compounds with a more flexible tail would have better binding to ATTP and consequently would have longer elimination halfâlife and, consequently, an increased exposure to drug, as measured by area under the plasma drug level versus time curve (AUC). This represents an enhanced residence of drug in the systemic circulation. Based on this hypothesis, we developed a new class of vitamin E analogues, the tocoflexols, which maintain the superior bioactivity of the tocotrienols with the potential to achieve the longer halfâlife and larger AUC of the tocopherols.